The Impact of English Educational Content on TikTok on Audience Understanding - Wayan Ulan Ade; Putu Ayu Asty Senja Pratiwi (Institut Penelitian dan Pengembangan Mandalika Indonesia (IP2MI), 2025)
TikTok is a social media platform that is not only used for entertainment but also as a learning medium, including for learning English. This study aims to explore the impact of English educational content on TikTok on users’ understanding. Data was collected through interviews with 10 respondents aged 18–24 who actively use TikTok to learn English. The results indicate that TikTok helps improve vocabulary acquisition, understanding of grammar, speaking skills and pronunciation skills, and overall comprehension of English. The platform is considered more engaging and relevant compared to traditional learning methods such as reading books.